INVESTMENT AND URBAN TOURISM INDUSTRY IN THE CITY OF CONSTANTINE - Haouari Souad (International Journal of Innovative Technologies in Social Science, 2024)
Global experiences have proven that tourism is one of the crucial economic sectors contributing significantly to the development process, owing to both material and non-material benefits it offers to host regions. Urban tourism, a contemporary type gaining momentum and support, has become increasingly popular in cities worldwide possessing essential tourism resources and attributes. This trend persists because urban tourism operates year-round, unaffected by seasonal or occasional variations. Tourism has evolved into a cornerstone of urban economies, leveraging local potentials to generate sustainable profits and bolstering economic growth. This strategic approach enables cities to assume multifaceted roles supporting development through the utilization of these capabilities. In this context, the concept of stimulating investment in Constantine’s tourism sector, which encompasses all the elements necessary for urban tourism—including religious, heritage, and natural attractions—is pivotal. However, the oversight, lack of foresight, and absence of strategic development plans from local authorities have prevented this sector from fulfilling Constantine’s esteemed position and potential. Consequently, this neglect has led to the squandering of a valuable economic asset that could otherwise bolster other sectors and drive the city’s development. To what extent and through what means can a sustainable tourism industry be cultivated in Constantine by capitalizing on its tourism potential?